2021
DOI: 10.1002/jae.2853
|View full text |Cite|
|
Sign up to set email alerts
|

Revisiting gender identity and relative income within households: A cautionary tale on the potential pitfalls of density estimators

Abstract: Any opinions expressed in this paper are those of the author(s) and not those of IZA. Research published in this series may include views on policy, but IZA takes no institutional policy positions. The IZA research network is committed to the IZA Guiding Principles of Research Integrity. The IZA Institute of Labor Economics is an independent economic research institute that conducts research in labor economics and offers evidence-based policy advice on labor market issues. Supported by the Deutsche Post Founda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
1
0
0
Order By: Relevance
“…For example, Bertrand et al (2015) reported that males outearn female partners in a far greater proportion of couples and that the fraction of couples in which the female's income exceeds the male's drops dramatically as the female's income increases above the 50% relative income threshold. This finding has been echoed in other research (e.g., Salland, 2018) although not universally (e.g., Kuehnle et al, 2021). The sharp inflection point at 50% indicates that females may be more accepting of situations in which they do not outearn males, obtaining lower-paying roles than they might otherwise be able to secure or leaving the labor force altogether (Bertrand et al, 2015).…”
Section: Earnings Within Dual-career Couplessupporting
confidence: 54%
“…For example, Bertrand et al (2015) reported that males outearn female partners in a far greater proportion of couples and that the fraction of couples in which the female's income exceeds the male's drops dramatically as the female's income increases above the 50% relative income threshold. This finding has been echoed in other research (e.g., Salland, 2018) although not universally (e.g., Kuehnle et al, 2021). The sharp inflection point at 50% indicates that females may be more accepting of situations in which they do not outearn males, obtaining lower-paying roles than they might otherwise be able to secure or leaving the labor force altogether (Bertrand et al, 2015).…”
Section: Earnings Within Dual-career Couplessupporting
confidence: 54%